Univariate and multivariate combined selection applied to hevea breeding - Costa, Reginaldo Brito da; Resende, Marcos Deon Vilela de; Araújo, Antonio José de; Gonçalves, Paulo de Souza; Bortoletto, Nelson (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this paper was to estimate the heritability coefficients by the univariate method and genetic prediction by the multivariate method, as well as to compare the genetic gain obtained by individual and combined selection between and within progenies, in rubber tree (Hevea brasiliensis Willd. ex Adr. de Juss.) Müell. Arg.). Twenty two half-sib progenies were established at the Experimental Station, in Votuporanga, São Paulo State, Brazil, following the randomized block design, with five replications and ten plants per plot. Three years after planting, number of latex vessel rings (NR), yield of dry rubber (YB), bark thickness (BT) and stalk circunference (SC) were evaluated. The results showed significant variability among progenies for YB, BT and SC characters. The heritability coefficients and genetic prediction to progenies level were high, with expressive values for the genetic prediction coefficients. Additional genetic gains were obtained by combined selection. Although the genetic gains had been small, this method is recommended, because it gives a better improvement and genetic gain. The most expressive values of improvement and genetic gain were estimated by multivariate method.